Analisis Penyaluran Tenaga Kerja oleh Perusahaan Outsorcing PT Gama Prima Karya Kepada PT. Fumakilla Indonesia - Krisanty; Sari Marlina; July Yuliawaty (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
i Currently, outsourcing is widely used intentionally to reduce labor costs with the protection and working conditions provided being far below what should be given. The role of outsourcing companies as facilitators in the distribution of labor becomes crucial in connecting job seekers with various available job vacancies. The purpose of this research is to understand the recruitment, selection, and distribution processes as well as to evaluate the performance of these workers at PT. Fumakilla Indonesia. This study uses a Descriptive Qualitative methodology by conducting interviews, observations, and documentation of the research data. The company has a minimum age requirement of 24 years, and the selection process itself involves several tests, namely a written test, a speed test, and an interview. After passing, an agreement letter from the company is made as proof of acceptance for work. Then, once the employees start working, their performance will be monitored to see whether their performance is satisfactory.